Evolution of neuropsychological profile in motor subtypes of multiple system atrophy. (January 2020) - Santangelo, Gabriella; Cuoco, Sofia; Picillo, Marina; Erro, Roberto; Squillante, Massimo; Volpe, Giampiero; Cozzolino, Autilia; Cicarelli, Giulio; Barone, Paolo; Pellecchia, Maria Teresa
Abstract: Introduction: Cognitive deficits and neuropsychiatric symptoms occur in parkinsonian and cerebellar subtypes of Multiple System Atrophy (MSA-P and MSA-C). These symptoms have been investigated mainly in cross-sectional studies. The present 1-year follow-up study aimed at evaluating the evolution of cognitive and neuropsychiatric profile in patients with MSA-C and MSA-P. Methods: Twenty-nine patients with MSA-P, 21 with MSA-C and 30 healthy subjects (HCs) underwent a neuropsychological battery and questionnaires assessing depression and apathy (T0). After 1 year (T1), patients with MSA-C and MSA-P underwent the same neuropsychological and neuropsychiatric tools employed at T0. Results: At T0, MSA-P and MSA-C groups were more depressed and apathetic and performed worse on tests assessing repetition abilities, executive and attentive functions than HCs. MSA-P and MSA-C groups did not differ on cognitive variables and neuropsychiatric scales. At T1, a significant worsening in spatial planning and psychomotor speed in MSA-C group and a significant worsening in memory, spatial planning, repetition abilities and functional autonomy in MSA-P group were found. The prevalence of apathy increased in both subtypes, whereas the prevalence of depression was reduced in MSA-C and relatively consistent in MSA-P. Conclusions: The finding revealed a wide-ranging worsening of cognitive functions in MSA-P and a significant decline in processing speed in MSA-C. These results underline the relevance of evaluating cognitive and psychiatric features of MSA over the course of the disease in the daily clinical practice. Highlights: A wide-ranging worsening of cognitive functions in MSA-P was found. A significant decline in processing speed in MSA-C was found. Assessment of cognitive and psychiatric features of MSA in clinical practice is relevant.